Potential of Green Leafhopper Attack (Empoasca sp.) in Tea Plantation Based on Climate Change Scenarios - Dwi Adelianingsih; Rini Hidayati; Yon Sugiarto (PERHIMPI (Indonesian Association of Agricultural Meteorology), 2019)
Pest growth is closely related to the climate conditions. This study aimed to analyze the impact of climate variability and climate change on the potential attack of green leafhopper (Empoasca sp.) on tea plantations at PTPN VIII Gunung Mas. The analysis was carried out to calculate the value of Ecoclimatic Index (EI) based on the functions of the compare years and the compare location in CLIMEX model. Pest suitability in the future was projected using RCP 4.5 and 8.5 climate scenarios, which were derived from MIROC 5 and CCSM 4 climate model outputs. The result indicated that Gunung Mas Tea Plantation was suitable for Empoasca sp. growth. The EI value (58) in the baseline year (2012-2017) confirmed the suitability. Climate variability influences the suitability for Empoasca sp. growth. During El-Niño, the EI value decrease substantially ( 26%). On the other hand, the EI value is projected to slightly increase in the future for both climate scenarios.